Constitutionalising Functional Independence: Constitutional Court Decision 121/PUU-XXII/2024 and the Future of Indonesia’s Civil Service Oversight - Andi Agung Mallongi; Anjas Saputra; Nur Zakinah Latif; Fitrah Dhani Prianto (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
This article examines how Constitutional Court Decision Number 121/PUU-XXII/2024 reconfigures the constitutional limits of legislative discretion in designing oversight of Indonesia’s State Civil Apparatus (ASN) following Law Number 20 of 2023. Employing doctrinal legal research through statutory, case-law, conceptual, and functional comparative approaches, it analyses the judgment alongside civil-service oversight arrangements in the United States, the United Kingdom, and Australia. The study finds that the 2023 reform did not abolish merit-system supervision, but reallocated it to executive institutions involved in ASN policy or administration, thereby reducing the institutional distance between policy-making, personnel management, and compliance review. The Court did not constitutionalise the former State Civil Apparatus Commission (KASN) as the only permissible model. It instead required institutionally separate oversight capable of securing functional independence. Open legal policy therefore continues to govern the supervisory institution’s name, organisational form, legal position, composition, and detailed allocation of powers, but no longer permits the elimination of substantive supervisory independence. The judgment may be characterised as a prospective institutional remedy with limited structural implications because it prescribes an independent institution and an implementation deadline while leaving its detailed design to the law-making authorities. The article conceptualises independent ASN oversight as horizontal accountability within the administrative state and develops an evaluative framework combining institutional independence, supervisory effectiveness, coordination, and democratic accountability. This framework distinguishes substantive implementation from the merely formal creation of a new supervisory body.